Molecular detection and risk factors of Eimeria in native and exotic chickens under varying management systems in Bangladesh - Md. Afazur Rahman; A R M Beni Amin; Kazi Farah Tasfia; Makoto Matsubayashi; Md. Shahiduzzaman (PLoS ONE, 2025)
A cross-sectional study was conducted in Bangladesh to determine the prevalence, molecular detection, and risk factors of Eimeria spp. infection in native and exotic chickens under various management systems. A total of 1,500 fecal samples were collected from different breeds, age groups, and sexes across multiple districts. Fecal examination using flotation and McMaster techniques identified positive cases, followed by molecular detection of Eimeria species. A questionnaire survey was also conducted to assess potential risk factors. Among the 1,500 chickens, 87 (5.8%) were positive for Eimeria oocysts, with higher prevalence in exotic breeds (7.96%) than native breeds (4.13%). The prevalence rates were 18.40%, 13.98%, 12.09%, and 3.40% in Aseel, Broiler, Sonali, and Deshi chickens, respectively, with no infection found in Naked Neck, Hilly, or Fayoumi breeds. Molecular analysis detected six Eimeria species: E. tenella was detected in 64 samples (62.07%) and in all breeds with the highest occurrence in Aseel. E. acervulina was the second most common species (25.28%), found in 23 samples from Deshi, Broiler and Sonali breeds. Other species, including E. brunetti, E. mitis, E. necatrix, and E. maxima, were rare and sparsely distributed. Chickens fed commercial feed (7.88%) had significantly higher infection rates (p < 0.0013) than those on local feed (3.99%). Intensive rearing systems (15.27%) showed higher infection rates compared to free-ranging systems, but no infection occurred in intensive systems without litter or semi-intensive systems. This is the first comprehensive report on infection status of Eimeria in chickens including all native breeds rearing in different management system in Bangladesh.